Factors Affecting the Decision of Customers' Decision to Use the Credit Services of Maruhan Japan Bank Lao Ltd, Luang Prabang Service Unit - SISOMEPHONE, Someluck (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
This study investigates the factors influencing customers' decisions to use credit services at Maruhan Japan Bank Lao Ltd, specifically at the Luang Prabang Service Unit. The primary aim is to analyze the impact of marketing mix elements and service quality on customers' decisions to use the bank's credit services. The study sample consisted of 199 customers who had used credit services at the Luang Prabang Service Unit. Data were analyzed using the SPSS statistical software to determine percentages, means, standard deviations, and through multiple regression analysis. The results indicate that marketing mix factors are significantly related to the decision to use credit services. Specifically, two marketing mix components were found to have a statistically significant positive effect at the 0.01 level. In terms of service quality, only one factor trustworthiness was found to significantly influence customers' decisions to use the credit services. Furthermore, the multiple regression analysis revealed that two service quality dimensions understanding the customer and responsiveness to customer needs also showed a positive correlation with the decision to use the services, with statistical significance at the 0.1 level.